Egg White Index, Egg Yolk Index, and Haugh Unit of Duck Eggs as Affected by the Dose of Carambola (Averrhoa bilimbi L.) Leaf Extract and Storage Durationaf Extract and Storage Duration - Devi Oktaviana; Soegeng Herijanto; Fani Dwi Evadewi (MEDIA PETERNAKAN, 2026)
This study evaluated the effect of the dose of carambola (Averrhoa bilimbi L.) leaf extract and of subsequent storage duration on the egg white index (EWI), egg yolk index (EYI), and Haugh unit (HU) of duck eggs. A completely randomised design in a 4 × 3 factorial arrangement was used, with extract dose as Factor A P0 (no soaking, control), P1 (5%), P2 (10%), and P3 (15%) and storage duration as Factor B 20, 30, and 40 days each of the 12 combinations replicated three times using 72 duck eggs in total. Eggs were soaked for 48 h, drained, and stored at room temperature; EWI and EYI were measured on a flat glass plate, HU was computed from albumen height and egg weight, and data were analyzed by ANOVA followed by least significant difference tests. Neither extract dose nor storage duration significantly affected EWI, EYI, or HU (P > 0.05), and no interaction was detected. Mean values nevertheless rose consistently with increasing dose and declined with longer storage: across doses EWI rose from 0.019 to 0.024, EYI from 0.267 to 0.364, and HU from 37.7 to 45.3, whereas extending storage from 20 to 40 days lowered EWI from 0.027 to 0.016, EYI from 0.373 to 0.245, and HU from 45.5 to 36.6. All values fell below the SNI 01-3926:2008 fresh-egg thresholds. Under the conditions tested the carambola leaf extract did not maintain duck-egg quality; alternative preservation materials are therefore recommended.